1997
DOI: 10.1103/physrevb.55.11138
|View full text |Cite
|
Sign up to set email alerts
|

Fraction of boroxol rings in vitreous boron trioxide

Abstract: The structure of vitreous boron trioxide (B 2 O 3 ) has been investigated by reverse Monte Carlo modeling using reported neutron and x-ray diffraction data. Structural models with different amounts of borons in boroxol rings were created using coordination and bonding constraints. The structure factors and the corresponding pair correlation functions of the models are generally in good agreement with the experimental neutron and x-ray data. However, the models containing large amounts of boroxol rings show sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
49
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 26 publications
7
49
1
1
Order By: Relevance
“…Molecular dynamics simulations that have been extended to radial distances beyond the coherence L extracted from Xray diffraction data, i.e., L = 2π/ Q 1 (Å −1 ), for SiO 2 [12], GeSe 2 [6], B 2 O 3 [23,24], and a-Se [13] have demonstrated that this range of radial distances in the MRO regime was necessary for the calculated contribution to S(Q) for the FSDP to replicate the experimentally determined S(Q) for the FSDP. This supports the interpretation for the coherence length and its relationship to an aspect of the MRO that relates to clustering that goes beyond the primitive ring structure, and in point of fact includes contributions of at least two primitive rings for SiO 2 and B 2 O 3 , as indicated in Fig.…”
Section: Bonding Constraints For Sro and Mromentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics simulations that have been extended to radial distances beyond the coherence L extracted from Xray diffraction data, i.e., L = 2π/ Q 1 (Å −1 ), for SiO 2 [12], GeSe 2 [6], B 2 O 3 [23,24], and a-Se [13] have demonstrated that this range of radial distances in the MRO regime was necessary for the calculated contribution to S(Q) for the FSDP to replicate the experimentally determined S(Q) for the FSDP. This supports the interpretation for the coherence length and its relationship to an aspect of the MRO that relates to clustering that goes beyond the primitive ring structure, and in point of fact includes contributions of at least two primitive rings for SiO 2 and B 2 O 3 , as indicated in Fig.…”
Section: Bonding Constraints For Sro and Mromentioning
confidence: 99%
“…Finally, a similar analysis of the contributions to the FSDP in B 2 O 3 [23][24][25] identifies the importance of differences between the local site symmetries of B, threefold coordinated planar bonding, and Si and Ge, fourfold coordinated tetragonal bonding that can contribute to qualitatively different π-bonding-geometry and symmetryspecific correlations that extend third and fourth nearest neighbor bond lengths into the length scale regime of MRO, and narrow them as well. [12].…”
mentioning
confidence: 96%
“…Wright and Sinclaire [5], Bray [6] and Zwanziger [7], found that 80% of boron atoms are included in the boroxol rings. Most molecular modeling studies [8,9] of B 2 O 3 came to different conclusions but generally the models could not reproduce the abundance of structural units building the borate network. Some improvements in the modeling of the borate network are the modifications introduced in the MD interactions by Cormack [10] leading to a relatively high fraction of 15-30% of boron in boroxol rings.…”
Section: Introductionmentioning
confidence: 96%
“…3 However, attempts to relate the presence of such structures with discernible features in the diffraction patterns lead to some recent controversies. In fact, results from calculations involving short-range structures only which portray most atoms as being involved in boroxol rings ͑about eighty percent͒ are confronted with attempts to reconstruct the structure of the glassy solid by means of Reverse Monte Carlo approaches, 4 where the best results are obtained if the percentage of boroxol rings is bounded below thirty percent ͑i.e., even the absence of any of those structures gives a better fit to experiment than those assuming a fraction of fifty percent or above͒. In fact, attempts to calculate the structure of vitreous B 2 O 3 using relatively small three-dimensional clusters of atoms forming boroxol rings have often encountered considerable difficulties when trying to reproduce the correct macroscopic density.…”
mentioning
confidence: 99%